Early Baldness in Males and Hormonal Changes - Baghdad Science Journal (مجلة بغداد للعلوم)
Androgenetic alopecia (AGA) or baldness is a common form of hair loss, affecting men more than women .The exact causes and pathogenesis of baldness are not well understood. A search for new drug is still needed. This study aims to evaluate the role of gonadotropins hormones in hair loss in males and its possibility to be used as treatment target. A total of 78 volunteers 43 with baldness and 35 healthy men were participated in this study. Their age ranged between (20-49) years, the studied groups were divided into two categories: firstly according to age (group1: 20-29 year), (group2: 30-39 year),and (group3: 40-49 year).Secondly according to baldness degree. LH and FSH were measured by using Enzyme Linked Immunosorbent Assay (ELISA) kits. The results showed a significant decrease (p